Consumer Knowledge and Product Variants on Buying Decisions for Herbalife RIZ Club Products in Palangka Raya City - Rita Yuanita Toendan; Hansly Tunjang (PT FORMOSA CENDEKIA GLOBAL, 2023)
This community service activity aims to increase purchasing decisions for Herbalife products in Palangka Raya City. The community service method used in this community service is descriptive quantitative. This community service was carried out using the Partial Least Square (PLS) analysis tool on 60 respondents who purchased Herbalife products in Palangka Raya City. The results of this community service show that (1) Consumer knowledge has a significant effect on the decision to purchase Herbalife products in the city of Palangka Raya, (2) Product variants have a significant effect on the product purchase decision on purchasing Herbalife products in the city of Palangka Raya. So that the results of this community service activity can be a reference for Herbalife to increase knowledge and focus on product variants, so that consumers can use products in a sustainable manner.